PENGARUH KONDISI PENGGORENGAN TERHADAP KUALITAS ROTAN MANAU (CALAMUS MANAN MIQ.) - Osly Rachman (Jurnal Penelitian Hasil Hutan, 1984)
The  effect  of  cooking  condition  on  the  quality  of rattan  is presented in  this article.  Round     fresh   manau   rattan  samples, each  of 100 cm in length and 3 cm in diameter were 80 stems  in all.The samples  were devided  into  4 groups before cooking. Each  group was cooked  with four different oil mixtures and four levels of cooking time.The results  reveal  that  the composition  of cooking  oils has a significant   effect  on  the  cane  color and  compressive strength  parallel to grain. but has no effect  on shear strength  of the rattan.The  mixtures  containing  coconut oil tends to reduce the  rate  of rattan  skin  color change  during  cooking.  Also,  such composition produced  better rattan skin  color in comparison with those treated with others.